Prevalence of lumpy skin disease and associated risk factors in beef cattle in Rembang Regency, Central Java, Indonesia - Yayan Taufiq Hidayat; Roza Azizah Primatika; Yatri Drastini (Veterinary World)
Background and Aim: Lumpy skin disease (LSD) is an economically devastating infectious disease in cattle. Rembang Regency, located in Central Java, Indonesia, has suffered over 3800 cases of LSD and 75 deaths since early 2023. This region holds the 4th number of most populous beef cattle producers in Central Java. However, until now, there have been no reports on the prevalence and risk factors related to LSD in beef cattle in Rembang Regency, Central Java, Indonesia. Therefore, this study aimed to estimate the prevalence of LSD and identify associated risk factors in Rembang Regency, Central Java, Indonesia.